Provision for the poor and the mission of the church: Ancient appeals and contemporary viability - Hays, Christopher M. (HTS teologiese studies, 2012)
Composed for the 2011 Prestige FOCUS Conference on Mission and Ethics at the University of Pretoria, this essay addressed the interrelationship between the New Testament conception of mission and one of the most significant moral topics in Scripture: the provision for the needy. In keeping with the investigative focus of the conference, the article began with an exegetical analysis of Matthew, Luke, the Pauline Epistles, James, and 1 John, demonstrating that generosity to the poor is an integral feature of these authors’ understanding of mission. The second half of the article investigated the rhetorical and theological strategies utilised by the aforementioned New Testament authors in motivating their readership to charitable action. Without aiming to be exhaustive, the article identified ten different strategies utilised by the New Testament texts in question: the authority of Jesus, the imitation of Christ, the theology of the cross, the imitation of the saints, equality, eschatological punishment, eschatological reward, earthly blessings, observing the Law, and love. The author not only described the ways in which these appeals functioned, but evaluated to what degrees and in which 21st century global Christian contexts these various appeals might be effective in motivating contemporary expressions of provision for the needy.